2019
DOI: 10.1371/journal.pone.0214807
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and causes of hospital maternal mortality in Tanzania: A 10-year retrospective analysis

Abstract: Background Maternal mortality is among the most important public health concerns in Sub-Saharan Africa. There is limited data on hospital-based maternal mortality in Tanzania. The objective of this study was to determine the causes and maternal mortality trends in public hospitals of Tanzania from 2006–2015. Methods and findings This retrospective study was conducted between July and December 2016 and involved 34 public hospitals in Tanzania. Information on causes of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
77
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 56 publications
(64 reference statements)
9
77
1
3
Order By: Relevance
“…The main indirect causes of maternal mortality were anemia (14.9%) and cardiovascular disorders (14.0%). The study also reported that there was an increasing trend of maternal deaths due to haemorrhage and cardiovascular disorders during the period [4]. Likewise, neonatal mortality rate in.…”
Section: Introductionmentioning
confidence: 76%
“…The main indirect causes of maternal mortality were anemia (14.9%) and cardiovascular disorders (14.0%). The study also reported that there was an increasing trend of maternal deaths due to haemorrhage and cardiovascular disorders during the period [4]. Likewise, neonatal mortality rate in.…”
Section: Introductionmentioning
confidence: 76%
“…A ten-year retrospective study undertaken in Tanzania reported that the leading cause of maternal mortality was eclampsia (34.0%), followed by obstetric haemorrhage (24.6%) and maternal sepsis (16.7%) [4]. The main indirect causes of maternal mortality were anaemia (14.9%) and cardiovascular disorders (14.0%).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research studies conducted in Tanzania highlighted a notable surge of maternal mortality ratio (MMR) (from 454 to 556 maternal deaths per 100 000 live births), while perinatal mortality ratio (PMR) slightly increased (36)(37)(38)(39) perinatal deaths per 1000 all total births) between 2010 and 2016 [6,7]. is incremental is related to some deficiencies in recognizing and managing obstetric complications that range from minor morbidity to lifethreatening conditions which need attention [8,9].…”
Section: Introductionmentioning
confidence: 99%